Revision of plausibility relations in dynamic systems - Simari, Patricio D. (2000)
An agent recieves information from the environment which usually includes other agents. Sorne of those agents could be providers of data. It is natural for the agent to maintain a certain arder among the informants based on the reliability or plausibility they show. In a dynamic environment that arder might change. In this work we present a model for representing changes on plausibility relations. The central idea is that the beliefs of an agent are provided by a set of informants, for which there is a plausibility relation. This relation establishes if sorne informants are more reliable than others. We propase change operators for the plausibility relation. We give postulates for these operators and define their construction.